Pendampingan Pembuatan Media Pembelajaran Inovatif Spinning Wheel Bagi Guru di Mi Miftahul Ma’arif - Amrini Shofiyani; Rina Dian Rahmawati; Khusnul Rahmawati; Nisa'atussalamah Nisa'atussalamah; Panji Ardiansyah (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2021)
Devotional activities in the community scheme of appropriate technology service courses (PPTTG) with the implementation of spinning wheel learning media in Miftahul Ma'arif with the aim of increasing the courage of students in speaking in front of other students know the types of learning media. Increase the enthusiasm and motivation of participants Students in following the learning process. Encouraging Teacher MI Miftahul Ma'arif in Balongombo Tembelang Village to develop learning media so that teaching and learning activities are more attractive and motivate students active in learning.